Treatment Effectiveness in Heart Failure with Comorbidity: Lung Disease and Kidney Disease - Gurwitz, Jerry H. (J Am Geriatr Soc, 2017)
OBJECTIVES: Recognizing the challenges of therapeutic decision-making for heart failure (HF) patients with comorbid conditions, our study objectives were to assess: (1) the clinical effectiveness of beta-blocker therapy in patients with HF and chronic lung disease; and (2) the clinical effectiveness of ACE inhibitors/angiotensin II receptor blockers (ARBs) in patients with HF and chronic kidney disease. DESIGN: Retrospective cohort study. SETTING: Large community-based cohorts of HF patients. PARTICIPANTS: Patients with HF with reduced ejection fraction (HFrEF) or HF with preserved ejection fraction (HFpEF). METHODS: We undertook separate new-user cohort studies to assess the effectiveness of: (1) beta-blocker therapy in HF and chronic lung disease; and (2) ACE inhibitors/angiotensin II receptor blockers (ARBs) in HF and chronic kidney disease. For the HF-chronic lung disease dyad group, we included patients who had a chronic lung disease diagnosis (ICD-9 codes 490-496, 518). For the HF-chronic kidney disease dyad group, we included patients who had an estimated glomerular filtration rate (eGFR) <60 ml/min/1.73m(2). The clinical outcomes of interest were death from any cause, hospitalization for HF, and hospitalization from any cause. We fitted pooled logistic marginal structural models (MSM) using inverse probability weighting, stratified by HF type. RESULTS: Among HFrEF patients with chronic lung disease, beta-blocker therapy was protective for death (RR 0.58, 95% confidence interval (CI) 0.44–0.77) and hospitalization for HF (RR 0.78, 95% CI 0.60–1.00). Among those with HFpEF, no statistically significant associations of beta-blocker therapy use with any of the outcomes were observed. We found ACE inhibitor/ARB use to be protective for all three outcomes of interest for patients with HFrEF including death from any cause, hospitalization for HF, and hospitalization from any cause (RR 0.60, 95% 0.40–0.91; RR 0.43, 95% CI 0.28–0.67; and RR 0.63, 95% CI 0.45–0.89, respectively), as well as for patients with HFpEF (RR 0.52, 95% CI 0.33–0.81; RR 0.35, 95% CI 0.18–0.68; and RR 0.67, 95% CI 0.47–0.95, respectively). CONCLUSION: Large observational studies may allow for the identification of important subgroups of the HF population that might benefit from existing treatment approaches. Our findings may also better inform the design of more definitive future observational studies and randomized trials.